2007
DOI: 10.1890/05-1935
|View full text |Cite
|
Sign up to set email alerts
|

Supply-Side Ecology in Mangroves: Do Propagule Dispersal and Seedling Establishment Explain Forest Structure?

Abstract: Abstract. Theory and empirical evidence suggest that spatial and temporal variation in propagule availability can have as great or greater an influence on community structure as post-recruitment biotic interactions, a phenomenon known as supply-side ecology. One of the first theories to invoke supply-side dynamics, D. Rabinowitz's Tidal Sorting Hypothesis (TSH), attributed the tidal zonation of mangrove tree species to the interacting effects of water depth and propagule size on dispersal and establishment. Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
103
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(124 citation statements)
references
References 106 publications
6
103
0
3
Order By: Relevance
“…We do however not fully support the TSH. Like the reassessment of the latter theory by Sousa et al (2007) indicated, propagule dispersal is not always directed towards areas more inland, but can be strongly concentrated towards the edges of lagoons and channels, as confirmed by the present study. This directional dispersal pattern is typical for areas with a small tidal range where high seasonal rainfall causes an additional flow of runoff that overwhelms any tendency for incoming tidal flow to carry propagules inland (Sousa et al, 2007).…”
Section: Propagule Dispersal From a Species Perspectivesupporting
confidence: 88%
See 3 more Smart Citations
“…We do however not fully support the TSH. Like the reassessment of the latter theory by Sousa et al (2007) indicated, propagule dispersal is not always directed towards areas more inland, but can be strongly concentrated towards the edges of lagoons and channels, as confirmed by the present study. This directional dispersal pattern is typical for areas with a small tidal range where high seasonal rainfall causes an additional flow of runoff that overwhelms any tendency for incoming tidal flow to carry propagules inland (Sousa et al, 2007).…”
Section: Propagule Dispersal From a Species Perspectivesupporting
confidence: 88%
“…Like the reassessment of the latter theory by Sousa et al (2007) indicated, propagule dispersal is not always directed towards areas more inland, but can be strongly concentrated towards the edges of lagoons and channels, as confirmed by the present study. This directional dispersal pattern is typical for areas with a small tidal range where high seasonal rainfall causes an additional flow of runoff that overwhelms any tendency for incoming tidal flow to carry propagules inland (Sousa et al, 2007). Moreover, species located along the edges of lagoons and channels, like in this case Avicennia officinalis, can drop their propagules directly into adjacent tidal creeks, allowing for dispersal over larger distances by currents if they remain buoyant.…”
Section: Propagule Dispersal From a Species Perspectivesupporting
confidence: 88%
See 2 more Smart Citations
“…Sediment accretion and erosion evidently influences the ability of propagules to disperse and establish, which therefore influences the spatio-temporal changes in mangroves (Clarke et al, 2001;Sousa et al, 2007). Most of propagules were found to disperse over a short distance up to tens of metres (McGuinness, 1997;Breitfuss et al, 2003;Sousa et al, 2007;De Ryck et al, 2012).…”
Section: Implication For Mangrove Management and Conservationmentioning
confidence: 99%